INFLUENCE OF GLUTARGIN ON INDICES OF METABOLIC INTOXICATION AT PATIENTS WITH TUBERCULOSIS OF LUNGS - Choporova, A.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Рresents the data about condition of oxidant-antioxidant systems, metabolic intoxication, connection of their pathological shifts with clinical manifestation of tuberculosis of lungs, biochemical signs of disturbances of liver function. It is shown, that the level МDA of blood allows to reliably judge about condition of the patient, current of disease, to predict quality of clinical treatment of tuberculosis and probability of development during polyсhemotherapy of biochemical shifts of signs of liver function. It is established, that application of glutargin in complex treatment of patients suffered from tuberculosis allows to eliminate displays of metabolic intoxication, make of correction of balance oxidant-antioxidant systems that can be regarded as confirmation of scientific validity of his clinical application.